2016
DOI: 10.1139/cjz-2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

The eggs of the apple snailPomacea maculataare defended by indigestible polysaccharides and toxic proteins

Abstract: The freshwater snails Pomacea Perry, 1810 lay conspicuous aerial egg clutches that are ignored by most predators. Egg biochemical defenses in the apple snail Pomacea canaliculata (Lamarck, 1822) are provided by multifunctional proteins. We analyzed the eggs of a sympatric species, Pomacea maculata Perry, 1810, studying the gross composition, toxicity, hemagglutinating activity, and its antinutritive and antidigestive properties. Eggs are mostly composed of polysaccharides (mainly galactogen) and proteins, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 61 publications
(106 reference statements)
1
41
0
8
Order By: Relevance
“…Nevertheless, P. diffusa and M. cornuarietis invest more on immune proteins and protease inhibitors. The three Pomacea species have a unique CaBP required for the formation of the calcareous shell of terrestrial eggs, and a Kunitz/Bovine pancreatic trypsin inhibitor that, at least in P. canaliculata and P. maculate , inhibit multiple digestive proteases of mice . In addition, duplication and positive selection of the CaBP and PV2 subunits were likely responsible for the aerial egg deposition and the evolution of the PV2 toxic protein as an anti‐predation mechanism in P. canaliculata and P. maculata .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, P. diffusa and M. cornuarietis invest more on immune proteins and protease inhibitors. The three Pomacea species have a unique CaBP required for the formation of the calcareous shell of terrestrial eggs, and a Kunitz/Bovine pancreatic trypsin inhibitor that, at least in P. canaliculata and P. maculate , inhibit multiple digestive proteases of mice . In addition, duplication and positive selection of the CaBP and PV2 subunits were likely responsible for the aerial egg deposition and the evolution of the PV2 toxic protein as an anti‐predation mechanism in P. canaliculata and P. maculata .…”
Section: Resultsmentioning
confidence: 99%
“…PV2, which constitutes around 7.5% of total PVF protein ? is a protein complex composed of two subunits: a membrane attack complex/perforin (MACPF) protein as the toxic subunit, and a tachylectin‐like protein as the delivery subunit, which are linked with a disulfide bridge . Laboratory experiments have shown that PV2 is neurotoxic to mice in P. canaliculata and probably is also a neurotoxin in P. maculata . However, the neurotoxicity was not observed in the PVF of P. scalaris , suggesting that PV2‐active toxins may not be present in all species of Pomacea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small hatchlings would be more vulnerable to predation by crayfish (Dorn & Hafsadi 2016), but the overall number of offspring potentially produced probably provides sufficient numbers to survive enhanced predation. Furthermore, the highly visible and seemingly vulnerable egg clutches are chemically defended and unpalatable to predators (Giglio et al 2016). Coupled with the climate and habitat in South Texas, all these factors (e.g., ability to overwinter, hundreds of propagules and egg defense) indicate the likely persistence and spread of this species.…”
mentioning
confidence: 99%